Understanding cowpea production, utilization and distribution dynamics in Malawi: a gendered perspective - Kampanje-Phiri, Jessica Jemima; Kafwambira, John; Mvula, Naomi; Chipeta, Michael M. (Frontiers in Sustainable Food Systems, 2025)
IntroductionCowpea (Vigna unguiculata L. Walp) is a vital legume in Sub-Saharan Africa, contributing significantly to food security and nutrition. Despite its potential, cowpea remains underutilized in Malawi. This paper examines the cowpea value chain with a strong focus on production, utilization and distribution in Malawi from a gendered perspective, highlighting the value chain actors’ roles and challenges faced by men, women and youth from farm to fork.Materials and methodsUsing a mixed-methods approach, data were collected from six districts through surveys, key informant interviews, and focus group discussions. The study analyzed the involvement of different actors in cowpea production, processing, and marketing through gender lenses and identified the constraints they face.ResultsThe findings reveal that women are actively involved in cowpea production but face constraints such as limited access to resources such as land and markets. The study also highlights the preference for local cowpea varieties among farmers and the specific traits they value by gender. Additionally, the active engagement of youth in cowpea production was noted, providing insights into their unique challenges and opportunities as they take part in this value chain.Discussion and conclusionThis study underscores the need for gender-sensitive interventions to enhance cowpea productivity and market access, ultimately improving household income and food security among different gendered groups. The research contributes to the thematic area “Processing and Preservation of Indigenous Food Crops: Sustainable Agenda for Nutrition Security in The Global South” by documenting potential opportunities and constraints in the production and utilisation of this indigenous crop that has a lot of potential to significantly improve food security and nutrition needs for Malawian farmers. It also explores the cultural values and gender roles that influence the use of this indigenous food crop, providing a comprehensive understanding of the socio-cultural dynamics at play across the whole cowpea value chain. The study further concludes that, by addressing gender-specific constraints and promoting indigenous knowledge, it offers valuable insights for developing future interventions related to promotion of cowpea production and creating a conducive policy environment that supports the equitable growth of the cowpea value chain in Malawi and beyond.